PENGARUH DESAIN PESAN DUA SISI PADA VIDEO TERHADAP PENGETAHUAN DAN PENILAIAN PETANI PADA GOOD AGRICULTURAL PRACTICES (GAP) BAWANG MERAH DI BANTEN - Vina Mahdalena; Pudji Muljono; Cahyono Tri Wibowo (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
The  structure  of  the  message  has  an  important  role  in  communication  persuasion  that  can  change  farmer’s knowledge and their perceived attributes of  innovations about Good Agricultural Practices (GAP) of shallot in Banten.  Two-sided  message  design  is  effective  in  changing  and  strengthening  one’s  attitude  according  to  the purpose of the message content because it has a balanced information between the advantages (positive) and the weaknesses  (negative).  The  purpose  of  study  is  to  analyze  the  two-sided  message  can  improve  farmer’s knowledge  and  change  their  perceived  attributes  of  innovations  about  GAP  of  shallot.  The  method  used  is experimental  model Solomon  four-group design  because of the  highest accuracy. This study was  conducted in Gempol Sari Village  involving 48  farmers divided  into four groups observation. The results  showed that there was no interaction between treatment and pretest, it can be ascertain that the changed by treatment. Furthermore, the design of a two-sided message in farmer video has proven to be effective improving their knowledge but has not  been  proven  to  change  perceived  of  innovations.  This  is  because  farmer’s  perceived  on  the  innovations pretest  already  in  the  favorable  category,  so that  when  given  the  treatment, their  perceived  still  remain  in  that category.  The  conclusion  of  the  study  shows  that  two-sided  message  video  can  improve  farmer’s  knowledge, while the pretest of perceived that originally was in the favorable category reach more higher score on posttest because of the treatment effect. Keywords: GAP, knowledge, perceived attributes of innovations, solomon design, two-sided message